Evaluating the Efficacy of a Polymerase Chain Reaction Assay for Pneumocystis carinii Detection in Respiratory Samples - Sonu Kumari Agarwal; Harendra Kumar Thakur; Bansidhar Tarai (Journal of Medical Evidence)
Introduction: Accurately identifying patients with pneumocystis pneumonia (PCP) presents considerable challenges, primarily relying on clinical suspicion. The manifestations of PCP lack specificity, encompassing symptoms such as cough, dyspnoea, fever, hypoxaemia, malaise and weight loss. Therefore, this study assesses the efficacy of a polymerase chain reaction (PCR) assay intended for use in clinical microbiology laboratories for the identification of Pneumocystis carinii from respiratory specimens. Materials and Methods: In this retrospective study, the medical records of patients aged 18 years and above were examined, focusing on those assessed using pneumocystis PCR-based tests. The study spanned from 2019 to 2022 in our tertiary care centre at Max Hospital, Saket. In this study, sputum and bronchoalveolar lavage (BAL) samples were proceeded for both staining and PCR for multi-copy mtLSU gene and single-copy dihydropteroate synthase polymorphisms (DHPS) fas gene of P. jirovecii. Results: In the analysis of 112 BAL specimens, 17 were identified as positive for P. carinii through both Grocott-Gomori’s Methenamine Silver Staining (GMS) staining and PCR. In addition, two BAL specimens were negative through GMS staining but showed positive results with PCR. On reviewing the clinical details of the patients associated with these two specimens, it was discovered that both individuals were under systemic steroid treatment, yet neither exhibited clinical signs of pneumocystis pneumonia (PCP). Consequently, these instances were classified as false positives by PCR. In comparison to GMS, the PCR assay demonstrated a sensitivity of 100% and specificity of 98% for detecting P. carinii in BAL specimens. Conclusions: The study underscores the necessity for individualised approaches, with each laboratory assessing the positive and negative predictive values based on their specific prevalence rates. In the ongoing pursuit of improving PCP diagnosis, PCR emerges as a promising screening tool that when used judiciously in conjunction with confirmatory measures, can enhance diagnostic precision in immunosuppressed populations.